Development of European Union and China Bilateral Trade After The 2008 Financial Crisis: A Cluster Analysis - Tastan, Serkan; Ozekicioglu, Halil (International Journal of Economics and Financial Issues, 2014)
<!– P margin-bottom: 0.08in; direction: ltr; line-height: 115%; widows: 2; orphans: 2; P.western font-size: 11pt; P.cjk font-size: 11pt; P.ctl font-size: 11pt; A:link color: rgb(0, 0, 255); A.western:link A.cjk:link A.ctl:link font-family: "Times New Roman"; –> China and European Union are two economic zones realizing a significant part of the world trade. These two economic zones have been subject to shrinkage after the 2008 crisis. The objective of this article is to reveal the status of foreign trade of both economic zones after the 2008 crisis by means of cluster analysis. In light of both export and import data, the countries are collected in three clusters and the only difference observed in cluster structures is that England is placed in the third cluster with Belgium, France, Netherlands, Spain and Italy in terms of export. Keywords: Trade Flows; Bilateral Trade; Cluster Analysis JEL Classifications: C38; F14; F15